The role of bilirubin in preventing the development of tobacco-induced lung cancer: a review / Nurnadia Majid, Hasseri Halim and Salfarina Ramli - Majid, Nurnadia; Halim, Hasseri; Ramli, Salfarina (Faculty of Applied Sciences, 2024)
The potent antioxidant properties of bilirubin and the inverse relationship between serum bilirubin level and cancer risk support the protective function of bilirubin, particularly in tobacco-induced lung cancer. 4-(Methylnitrosamino) -1-(3-pyridyl)-1-butanone (NNK) is one of the procarcinogens in tobacco smoke that requires metabolic activation to form its metabolite; 4-(methylnitrosamino) -1-(3-pyridyl) - 1-butanol (NNAL). The activation produces free radicals with DNA-damaging properties. From the findings of previous studies, it can be deduced that bilirubin prevents the development of tobacco-induced lung cancer by directly scavenging free radicals derived from tobacco product smoke and inhibiting cytochrome P450 2A6 and 2A13- mediated NNK metabolism. Furthermore, as an endogenous substrate of CYP2A6, bilirubin affects the expression and hydroxylation activity of CYP2A6, but the impact of bilirubin on CYP2A13 has yet to be investigated in detail. More research is necessary to elucidate the impact of bilirubin on NNK and NNAL metabolism mediated by both enzymes. Consequently, this review describes the current status and potential capabilities of bilirubin. The ongoing research gaps and areas for future research are highlighted.